Vegetable Plants with Water Treatment Potential: A Review - Jones, Alfred N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Chemical coagulants and flocculants have been used for decades in water treatment. However, because of cost issues associated with the entailment of importation importing of these chemicals, developing countries were left with no other option than to rely on contaminated water for their domestic consumptions. In view of this, some communities used their ingenuity and successfully employed natural plant and animal products to purify their water supply. In many instances, these products were found to achieve comparable water quality results to that of the conventional chemicals. The aim of this study was to evaluate some of the different plant genera that have been tested in water treatment. Their advantages and setbacks are highlighted. Most notably, some of these natural extracts performed double functions as a coagulant and as disinfectant. Conversely, several research works have pointed out that the main drawback of using natural extract in water treatment is the addition of organic compounds in the treated water which makes it unfit for human consumption due to change in taste, color, and odor. This drawback was, however, overcome in some studies where the materials were purified to obtain only the coagulant compounds. Therefore, the use of natural extracts in drinking water treatment would bring relief to many inhabitants in developing countries in terms of access to clean drinking water. Additionally, the study recommends further investigation into disinfecting the treated water with chlorine to assess their disinfectant by-products (DBPs) formation.